The Effect Of Implementing The Interval Method Using Weighted Vest On Power Endurance Abbilities Pusaka Angel’s Players - Yusup, Ayi Mohamad; Agus, Herdiansyah; Yudiana, Yunyun; Sidik, Dikdik Zafar (Journal of Sport Science and Education, 2021)
Power endurance capability is needed by players to maintain explosivity in a tired state. Both explosivity in running and technical explosivity in the game. To increase the power endurance ability, at the interval of the match after the first week the Pusaka Angel coach team provides training using the interval method accompanied by the use of a weighted vest. The use of the interval method because this method is one of the training methods that can increase the ability of power endurance. The research method is to process thevariable data identified from the test results and measurements of the power endurance ability of the women's futsal athletes from the Pusaka Angel team. relationship and the level of relationship made to events that have taken place or have occurred. This was done untreated for 8 weeks. The target population in this study were all female futsal athletes from the Pusaka Angel team. Meanwhile, the affordable population is determined by athletes prepared to participate in the 2019/2020 Indonesian Professional Futsal League, totaling 17 female athletes. Based on data processing and statistical analysis in this study, it can be concluded that there is a significant effect of the application of the interval method using a weighted vest on increasing the power endurance ability of the heirloom futsal players.